The Brazilian Portuguese version of the Work Productivity and Activity Impairment – General Health (WPAI-GH) Questionnaire - Ciconelli, Rozana Mesquita; Soárez, Patrícia Coelho de; Kowalski, Clarissa Campos Guaragna; Ferraz, Marcos Bosi (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: It is still difficult to measure work productivity losses caused by health problems. Despite the importance given to this issue over the last few years, most instruments for performing this task are available only in the English language. This study translated the Work Productivity and Activity Impairment – General Health (WPAI-GH) Questionnaire into Brazilian Portuguese, adapted it cross-culturally and evaluated its reliability and validity. DESIGN AND SETTING: Cross-sectional survey to test scale reliability and validity, at São Paulo Hospital and the clinic of the Rheumatology division of Universidade Federal de São Paulo — Escola Paulista de Medicina (Unifesp-EPM). METHODS: Data were obtained from a survey that incorporated the WPAI-GH, short form-36 (SF-36) and some demographic questions. The questionnaires were administered by interview to 100 subjects. RESULTS: Descriptive statistics was used to characterize the subjects. The intraclass correlation coefficient and Cronbach’s alpha were used to assess the reliability and internal consistency of the instrument. Intraclass correlation coefficients from 0.79 to 0.90 indicated good reliability. Cronbach’s alpha of 0.74 indicated good inter- nal consistency. Pearson’s correlation coefficient was used to assess validity. There were significant positive relationships between the WPAI-GH and SF-36. CONCLUSION: The Brazilian Portuguese ver- sion of the WPAI-GH is a reliable and valid measurement tool and may be useful for those who seek to measure the impact on productivity of health problems among populations of Brazil- ian employees.